Investing in public health: A new age for globalization of solidarity and cooperation - Belkis Romeu (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Health as a public good is a collective good, a right for all, a right that social, economic and political actors in each country must defend and preserve. It is an inalienable right of the people, non-negotiable and whose enjoyment is not supported by any rivalry [1].